Simulation Study on Interactive Propagation of Hydraulic Fractures and Natural Fractures in Shale Oil Reservoir - Tian, Fuchun; Jin, Yan; Shi, Lin; Cong, Ziyuan; Li, Yuwei (Frontiers in Earth Science, 2022)
Natural fractures are developed in the shale oil reservoir, and hydraulic fracture (HF) morphology is complex. The fracture shape can be inverted by using fracture propagation numerical simulation technology, which provides guidance for fracturing parameter design and fracturing process optimization. However, the existing models still have many deficiencies in the interactive propagation mechanism of HF and natural fracture (NF). Based on the three interactive modes of HF and NF (HF propagation without NF, HF propagation with full NF, HF propagation with half NF), this paper establishes the fracture propagation model and puts forward the simulation calculation method. Brinkman equation is used to modify the leakage model based on Darcy's law, and G1701H Well is taken as an example to simulate the fracture propagation law under different interaction modes. The research shows that there is a transition region between the HF wall and rock matrix. The greater the porosity and permeability of the rock matrix, the more significant the influence of the transition region on leakage. The NF zone will change the propagation direction of the main fracture. When there are multiple clusters of fractures in the same fracturing section, only some HF meet with natural fractures, it is easy to form a "T" shaped fracture network. The results improve the existing hydraulic fracturing model and provide help for fracturing parameter design and fracture parameter inversion of the shale oil reservoir.